Climate change and Australia. (9th October 2013) - Head, Lesley; Adams, Michael; McGregor, Helen V.; Toole, Stephanie
<x xml:space="preserve">Abstract</x> Australia has had a variable and mostly arid climate as long as humans have been on the continent. Historically observed trends toward increased warming, with rainfall increases in many tropical areas and rainfall decreases in many temperate areas, are projected to continue. Impacts will be geographically variable but mostly negative for biodiversity, agriculture, and infrastructure. Extreme events such as bushfires and floods will increase in frequency and intensity, concentrated in summer. With an economy heavily dependent on coal for domestic electricity generation and as an export commodity, Australians are high per capita contributors to anthropogenic climate change. A quarter‐century of steps to mitigation led in 2012 to a carbon price that has the long‐term potential to shift the economy toward more renewable energy sources. However as in other parts of the world this change has come too late, and is proceeding too slowly, to avoid significant climate change. A heritage of indigenous adaptation, strong volunteer cultures, and contemporary cultural diversity provide Australia with considerable adaptive capacity for gradual changes, but the nation is underprepared for sudden or step changes. We identify four pressing research and policy needs focused on such changes: (1) systematic attention to processes and impacts of negative transformative change, or worst‐case scenarios, (2) improve forecasts of year‐to‐year rainfall and climate variability, focusing on processes and climate drivers that may change in response to higher greenhouse gases, (3) identification and engagement of diverse cross‐cultural resources, and (4) articulation of alternative governance mechanisms that can interact dynamically with strong government. WIREs Clim Change 2014, 5:175–197. doi: 10.1002/wcc.255 Conflict of interest: The authors have declared no conflicts of interest for this article. For further resources related to this article, please visit the WIREs website.